Social Knowledge and Signals in Primates. Issue 7 (10th December 2012) - BERGMAN, THORE J.; SHEEHAN, MICHAEL J.; Higham, James P.; Semple, Stuart
<x xml:space="preserve">Abstract</x> Primates are notable for having a rich and detailed understanding of their social environment and there has been great interest in the evolution and function of social knowledge in primates. Indeed, primates have been shown to have impressive understandings of not only other group members but also the complex relationships among them. To be useful, however, social knowledge requires memories from previous encounters and observations about individual traits that are stable. Here, we argue that social systems or traits that make social knowledge more costly or less accurate will favor signals that either supplement or replace social knowledge. Thus, the relationship between signals and social knowledge can be complementary or antagonistic depending on the type of signal. Our goal in this review is to elucidate the relationships between signals and social knowledge in primates. We categorize signals into three types, each with different relationships to social knowledge. (1) Identity signals directly facilitate social knowledge, (2) current‐state signals supplement information gained through social knowledge, and (3) badges of status replace social knowledge. Primates rely extensively on identity information, but it remains to be determined to what extent this is based on receiver perception of individual variation or senders using identity signals. Primates frequently utilize current‐state signals including signals of intent to augment their interactions with familiar individuals. Badges of status are rare in primates, and the cases where they are used point to a functional and evolutionary trade‐off between badges of status and social knowledge. However, the nature of this relationship needs further exploration. Am. J. Primatol. 75:683‐694, 2013. © 2012 Wiley Periodicals, Inc.